Assessment of genetic diversity and wilt disease resistance in hot pepper (Capsicum annuum) germplasm from Ethiopia - Woubit, Dawit Bedane; Eleni, Shiferaw; Fitsum, Sileshi; Mekonnen, Assefa; Shimeles, Aklilu (Biodiversity: Research and Conservation, 2021)
Hot pepper (Capsicum annuum L.) is an economically important crop in Ethiopia. Wide variability in hot pepper germplasm in Ethiopia is expected due to the presence of diverse environmental conditions and variation in farming systems. The present study was carried out to evaluate the resistance of 75 hot pepper accessions to wilt disease and assess their genetic diversity using SSR markers. Out of 75 accessions tested, the present study identified 23 accessions that showed resistance (R) with the value of 1-10% disease incidence. The genetic diversity assessment using 13 polymorphic SSR markers allowed the detection of 111 clear and scorable bands. The number of alleles per locus ranged from 5 to 13, with an average of 8.54. The PIC value ranged from 0.27 to 0.87 with an average of 0.59. The gene diversity indices were highly variable across SSR loci and ranged from 0.29 to 0.88 with mean genetic diversity of 0.62. Observed heterozygosity was also highly variable between loci (0.01-0.45) indicating that the accessions were not fixed to homozygosity. Furthermore, genetic diversity parameters were estimated among populations by grouping accessions based on their origin. Within populations, the PIC value ranged from 0.31 to 0.77. The genetic distances among the eight populations ranged from 0.15 to 0.48. The observed highest genetic diversity (0.80) in the Amhara region (Gojam) may indicate this area as the primary site for designing in situ conservation for this crop in Ethiopia. The research findings provide baseline information on disease resistance germplasm sources to be used for the breeding program, as well as the status of genetic diversity of the accessions for efficient conservation and proper utilization of the existing genetic resources in the country.